Gravity analysis for subsurface characterization and depth estimation of Muda River Basin, Kedah, Peninsular Malaysia - Zakariah, M.N.A. (MDPI AG, 2021)
Gravity survey is one of the passive geophysical techniques commonly used to delineate geological formations, especially in determining basement rock and the overlying deposit. Geologically, the study area is made up of thick quaternary alluvium deposited on top of the older basement rock. The Muda River basin constitutes, approximately, of more than 300 m of thick quaternary alluvium overlying the unknown basement rock type. Previous studies, including drilling and geo-electrical resistivity surveys, were conducted in the area but none of them managed to conclusively determine the basement rock type and depth precisely. Hence, a regional gravity survey was conducted to determine the thickness of the quaternary sediments prior to assessing the sustainability of the Muda River basin. Gravity readings were made at 347 gravity stations spaced at 3â5 km intervals using Scintrex CG-3 covering an area and a perimeter of 9000 km2 and 730 km, respectively. The gravity data were then conventionally reduced for drift, free air, latitude, Bouguer, and terrain corrections. These data were then consequently analyzed to generate Bouguer, regional and total horizontal derivative (THD) anomaly maps for qualitative and quantitative interpretations. The Bouguer gravity anomaly map shows low gravity values in the north-eastern part of the study area interpreted as representing the Main Range granitic body, while relatively higher gravity values observed in the south-western part are interpreted as representing sedimentary rocks of Semanggol and Mahang formations. Patterns observed in the THD anomaly and Euler deconvolution maps closely resembled the presence of structural features such as fault lineaments dominantly trending along NW-SE and NE-SW like the trends of topographic lineaments in the study area. Based on power spectral analysis of the gravity data, the average depth of shallow body, representing alluvium, and deep body, representing underlying rock formations, are 0.5 km and 1.2 km, respectively. The thickness of Quaternary sediment and the depth of sedimentary formation can be more precisely estimated by other geophysical techniques such as the seismic reflection survey. Â© 2021 by the authors.